The Effect Of Price Perception And Service Quality On Purchase Decision At Asep Stroberri Restaurant (ASSTRO) Tasikmalaya : - Haloho, Windy Cindyana; Sutrisna, Arga; Arif, Arif (Jurnal Multidisiplin, 2024)
This study aims to determine the effect of Price Perception and Service Quality on Purchasing Decisions at Asep Stroberri Restaurant Tasikmalya. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analysis tool used in this study is multiple linear regression analysis using SPSS version 25. Based on the results of this study, it shows that Price Perception and Service Quality simultaneously have a positive and significant effect on Purchasing Decisions. Price Perception partially has a significant effect on Purchasing Decisions. Service Quality partially has a significant effect on Purchasing Decisions.